"Economies of Experience"—Disambiguation of Degraded Stimuli Leads to a Decreased Dispersion of Eye‐Movement Patterns. (20th November 2017) - Król, Magdalena Ewa; Król, Michał
Abstract: We demonstrate "economies of experience" in eye‐movement patterns—that is, optimization of eye‐movement patterns aimed at more efficient and less costly visual processing, similar to the priming‐induced formation of sparser cortical representations or reduced reaction times. Participants looked at Mooney‐type, degraded stimuli that were difficult to recognize without prior experience, but easily recognizable after exposure to their undegraded versions. As predicted, eye‐movement dispersion, velocity, and the number of fixations decreased with each stimulus presentation. Further analyses showed that this effect was contingent on recognition, and the selection of information from the stimulus could be informed by the identity of the presented object. Finally, our study demonstrates that after exposure to the undegraded version of the stimulus, eye‐movement patterns associated with its degraded and undegraded versions become more similar. This suggests that eye‐movement patterns can evolve to facilitate the optimal processing of a given stimulus via experience‐driven perceptual learning.